Host adaptation of Mycobacterium tuberculosis and Mycobacterium bovis: a genomic and transcriptional approach - Zimpel, Cristina Kraemer (2022)
Tuberculosis (TB) is caused by the Mycobacterium tuberculosis complex (MTBC), a bacterial group of clonally evolved pathogens that infect humans and animals. Despite a high genetic similarity, MTBC members demonstrate different host tropism and virulence. While Mycobacterium tuberculosis is the main causative agent of human TB and is highly adapted to this host species, Mycobacterium bovis has a broader host range with variable populational persistence. In order to provide insights into phenotypic differences between both pathogens, this four-chapter thesis was developed with two major aims: (i) to perform a phylogenomic analysis to understand the populational structure of M. bovis isolated from cattle and wildlife worldwide and to provide dating estimates for the origin of this pathogen; and (ii) to compare the global transcriptional profiles of M. bovis SP38 and M. tuberculosis H37Rv in vitro and identify their activated metabolic pathways using flux balance analysis (FBA) coupled with transcriptomics. First, the phylogenomic analysis, including approximately 2,000 M. genomes from 23 countries, identified at least four distinct lineages of M. bovis (Lb1, Lb2, Lb3, and Lb4) underlying the current disease distribution. These lineages clustered according to geographical origin and clonal complexes (CC), but not host species. Additionally, data divergence analysis indicates that extant M. bovis originated between 715- and 3,556-years BP (before present), with later emergence in the New World and Oceania, likely influenced by trades among countries. Next, RNA-seq from M. tuberculosis and M. bovis grown in vitro showed significant differences involving genes related to cell wall metabolism, with upregulation of PDIM (phthiocerol dimycocerosates) in M. bovis, and upregulation of SL-1 (sulfolipid), trehalose lipids, and glycolipids in M. tuberculosis. Among the top expressed genes, SigK regulon and secretion system ESX-1 were upregulated in M. bovis, while genes of the nitrate metabolism and toxin-antitoxin systems were upregulated in M. tuberculosis. Furthermore, FBA suggests major differences in central carbon metabolism between species, particularly in the use of glutamate to fuel the GABA shunt in M. tuberculosis, but cysteine production in M. bovis. We speculate that some of these differences occur because M. bovis is a microaerophile and M. tuberculosis an obligate aerobe. In conclusion, the studies reported herein greatly expanded our knowledge of the populational structure of M. bovis and its metabolism in comparison to the model organism M. tuberculosis. These results will serve as basis for further research related to the use of genomics to understand disease transmission and virulence, as well as to how these mycobacteria respond to microenvironmental conditions that can sustain their virulence and host tropism traits.